Basic Skills in Higher Education: An Analysis of Attributed Importance - Aranda, Lourdes; Mena-Rodríguez, Esther; Rubio, Laura (Frontiers in Psychology, 2022)
Today, the skills-based approach is increasingly in demand by companies due, in large part, to the fact that it favors the management of human resources by focusing on individual capabilities. In this way the relationship between similar jobs is improved. As a result, choosing the right candidates has become increasingly selective. Universities, therefore, need to teach skills to improve the incorporation of graduates into the workplace making it as successful as possible. The main objective of this study was to analyze and compare the importance assigned to the acquisition of basic skills in the university education of 694 students studying four different bachelor degrees: pedagogy, early childhood education, primary education, or psychology. For this purpose, a Likert-type questionnaire on basic skills was distributed with four possible options and the following five dimensions that grouped basic skills: organizational and planning capacity; access to information sources; analysis and synthesis of texts, situations, and people; teamwork; and problem solving. The results show that as a whole all students across different bachelor degrees gave a high score to the acquisition of basic skills, with early childhood education students giving it greater importance compared to the students from other disciplines and, more specifically, differences were observed in some dimensions depending on the bachelor degree that they have started.